Organic rankine cycle as an option in microturbine combined cycle power generation [electronic resource] - 421289 Thum, Xin Jing (2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2007